Improving Reading Skill Using Jamboard for Senior High School Students - Ramadhani, Talitha Ayu (RETAIN : Journal of Research in English Language Teaching, 2022)
This study aimed to determine whether the Jamboard can improve the reading abilities of senior high school students. This research employed a quantitative approach. This research was conducted using a pre-experimental design. This study utilized only one class group. Hence there was no experimental class and no control class. The instruments used in this investigation are the pre-test and post-test. The researcher designed the instructional materials, lesson plan, pre-and post-tests, and the media. Both the pre-test and post-test were presented in G-form. The pre-and post-tests comprised four texts and twenty questions in total. The pre-test was administered before administering treatment to the students, whereas the post-test was issued after the treatment. The treatment consisted of four sessions. This investigation was conducted at a private senior high school in Surabaya, with the participation of 12 tenth-graders. The post-test scores of the students were much higher than their pre-test scores. The mean of the pre-test score was 42.92 and 75.42 for the post-test, and the data indicated that this media had a significant effect size on the students' reading abilities because it has a value of 2.3 from the standard that has been set, which is <0.5. Therefore, it can be concluded that Jamboard media can help improve students' reading ability because the data results show a significant increase in student scores. Also, the researcher suggests that this Jamboard media can be used to teach students how to read because it has a positive effect on both teachers and students as they learn.